Dairying as an Instrument for Ensuring Socio-Economic and Nutritional Security in Rural India - Ayush Kumar and Jignesh Shah (Ind. Jn. of Agri. Econ., 2016)
It is often said that dairying is one of the best poverty alleviation tool but this claim is seldom backed by appropriate nationwide large scale data. The unit-level data from the Consumer Expenditure Survey, conducted by National Sample Survey Organisation, shows that the households which are engaged in dairying are comparatively better-off both in terms of financial and nutritional security when compared to the households which are not engaged in dairying in the rural areas. After categorising the households into five groups of poor, lower middle, middle middle, upper middle and rich, based on their monthly per capita expenditure (MPCE), the percentage of households in the bottom two categories is substantially lower in case of households engaged in dairying than those which are not. Also, the producer households consume more milk than the non-producer households especially in the bottom categories thus ensuring nutritional security. Dairying may prove to be one of the best tools for poverty alleviation, nutritional security and changing the socio-economic milieu of rural India.